General Practitioners’ Autonomy in the Management of Non-Communicable Diseases (NCDs) in the JKN Era: Is It Feasible? - Nur Afrainin Syah (Faculty of Medicine, Public Health, and Nursing, 2019)
Demographic, epidemiological, and nutritional transitions increase life expectancy, changes in lifestyles and behaviors of Indonesian people. These changes are resulting in a growing contribution of non-communicable diseases (NCDs) to morbidity and mortality, especially metabolic disorders, such as type 2 diabetes mellitus (DM), hypertension, and dyslipidemia. Approximately 10.9% of the Indonesian population above 15 years old suffers from type 2 DM (21.2 million) and 34.1% have hypertension (66.3 million) in 2018. These figures increase significantly from 2013 figure; 6.9% and 25.8% respectively1. The metabolic disorders, which in turn, are responsible for vascular problems such as renal failure, stroke, and heart attack. Not surprisingly, then, 60% of Indonesian national health insurance (JKN) funds are spent on the NCDs. This condition causes a deficit and threatens the sustainability of the JKN program.